Blended Learning Model for Science Education: A Literature Review - Ni Made Yeni Suranti; Ibrahim Ibrahim (Indonesian Publication Center, 2024)
Blended learning is a learning model that integrates online and face-to-face learning to create a flexible and interactive learning experience. This article examines the application of blended learning in science education through the descriptive content analysis study method. This method describes the findings of various relevant scientific articles, analyzes the relationship between these findings, and identifies the principles of the blended learning model. Data were obtained from articles published in national and international journals, then identified, described, and analyzed to provide an in-depth picture of the implementation of blended learning in science learning in elementary schools. The literature review results show that blended learning can improve students' conceptual understanding, critical thinking skills, and learning motivation in science learning. Combining online learning through virtual simulations and digital experiments with face-to-face learning enriches students' learning experiences. However, the success of implementing this model depends on the readiness of infrastructure, teacher skills, and balanced learning design. This article concludes that blended learning has great potential to improve the quality of science learning in elementary schools, provided that existing challenges can be overcome.